METRONIDAZOLE (1%) AND CHLORHEXIDINE (0.25%) GEL AS AN ADJUNCT TO SCALING AND ROOT PLANING IN THE TREATMENT OF MODERATE TO SEVERE CHRONIC PERIODONTITIS—A CLINICAL STUDY. - Hussain, Dr Huda; Jan, Prof.(Dr.) Suhail Majid; Behal, Dr. Roobal (Journal of Biomedical and Pharmaceutical Research, 2019)
Metronidazole and Chlorhexidine are commonly employed antimicrobial agents in the antinfective stage of periodontal therapy, used with the aim to achieve complete eradication of the pathogenic flora from the subgingival niches, in conjunction with professional debridement. This study was aimed to determine the adjunctive effect of a novel combination of metronidazole (1%) and chlorhexidine (0.25%) in a gel form for management of moderate to severe chronic periodontitis. Twenty subjects were included for a split mouth prospective study. Gingival index, Plaque Index, Bleeding scores and Probing depth were noted at baseline, 2 weeks and 1 month after scaling and root planing with or without an additional subgingival delivery of the antimicrobial gel. An improvement of periodontal health was seen after therapy, and the difference between the test and control sites was significant for sites with an initial probing depth of 6-8mm. However, for deeper pockets (>8mm) the difference was statistically non-significant. The reduction in bleeding score was sustained at the test sites throughout the study period. It was concluded that the adjunctive use of metronidazole (1%) and chlorhexidine (0.25%) gel could provide clinical benefit for the management of deep pockets uptil 8mm of initial probing depth.